Developing a Model for the Establishment of the Hospice Care Delivery System for Iranian Adult Patients With Cancer - Beiranvand, Samira; Rassouli, Maryam; Hazrati, Maryam; Molavynejad, Shahram; Hojjat, Suzanne; Zarea, Kourosh (Frontiers in Psychology, 2022)
Introduction Making appropriate plans for the provision of hospice care is considered a perceived need in the Iranian health system. The current study aimed to develop a model for establishing hospice care delivery system for the adult patients with cancer. Materials and Methods This study is part (data of the third and fourth phases) of a larger study that has been done in four phases. This Health System Policy Research (HSPR) utilized a mixed qualitative-quantitative approach. At the first phase, a qualitative study was conducted which explained the care needs and the requirements for establishing this system from the stakeholders’ perspective (directed content analysis). The second phase aimed to examine the current situation of hospice care delivery in Iran and identify and determine the similarities and differences among them in the selected countries (comparative study). At the third phase, the main areas of the model and the related indicators were extracted and prioritized by consulting with experts (Delphi survey). Then the model was formulated. At the fourth phase, the proposed model was validated and finalized in terms of importance, scientific acceptability, and feasibility. Results Based on the developed model the first and the most important step in establishing the hospice care delivery system is laying the groundwork in the health system which requires focusing on policymaking. It is necessary to establish hospice centers and implement public awareness raising programs, train, and supply expert manpower, strengthen family physician and referral process, formulate clinical guidelines, encourage the private sector and NGOs(Non-Governmental Organizations (NGOs).) to invest, develop end-of-life and hospice care service packages, and create quality care indicators. The proposed model had moderate feasibility. Conclusion This model was developed based on the current Iranian healthcare structure and the needs of terminally ill cancer patients. It can be used as a model tailored to the current state of the health system and community in Iran. It is suggested to use this model as a pilot at the regional level.